Understanding Commuting Decisions: A Case Study of Students and Staff at McMaster University - Becker, Jessica S. (My University, 2007)
This thesis outlines the methods, results, recommendations, and conclusions of a study conducted on the parking problem at McMaster University in Hamilton, Ontario, Canada. By taking the approach of studying the commuting behaviours undertaken by the staff and the students, this study not only is the first conducted at the university to connect travel behaviours with a parking problem, it is also able to provide meaningful recommendations towards successful travel demand management (TOM) that will help alleviate the parking crunch. A variety of research methods were employed including some exploratory analysis, employing Geographical Information Systems, and multivariate statistical analysis. Results are compared with relevant literature to produce recommendations towards the components of a well-developed TOM scheme, the most important of which are to employ many strategies simultaneously, and to have regular public input. The thesis concludes by summarizing the most easily employed strategies, implemented outside of the large-scale TOM plan, that would entice drivers to switch to altemative transportation modes of personal cars.
Keywords: Geography; Geography